2009
DOI: 10.1377/hlthaff.28.4.1056
|View full text |Cite
|
Sign up to set email alerts
|

Borrowing And Selling To Pay For Health Care In Low- And Middle-Income Countries

Abstract: Many families around the world make sizable out-of-pocket payments for health care. We calculated the frequency of borrowing money or selling assets to buy health services in forty low-and middle-income countries and estimated how various factors are associated with these coping strategies. The data represented a combined population of 3.66 billion, or 58 percent of the world's population. On average, 25.9 percent of households borrowed money or sold items to pay for health care. The risk was higher among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
190
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(207 citation statements)
references
References 26 publications
12
190
0
4
Order By: Relevance
“…As predicted -partly from the results of previous studies 9,14,17 -the risk that a household will need to implement distress financing to cope with the costs of health care was found to increase as the wealth of the household decreased. The high costs of inpatient care appeared to pose particular difficulties for many of the study households and a loan was often needed.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As predicted -partly from the results of previous studies 9,14,17 -the risk that a household will need to implement distress financing to cope with the costs of health care was found to increase as the wealth of the household decreased. The high costs of inpatient care appeared to pose particular difficulties for many of the study households and a loan was often needed.…”
Section: Discussionsupporting
confidence: 55%
“…10 In the few relevant studies that have been conducted, the coping strategies that are followed have been found to differ with the type of disease involved, 6,7,[11][12][13] with the sector (private or public) providing the outpatient facilities used, if any, 9,14 with the need for inpatient care, [14][15][16] and with the economic status of the patients or their households. 9,10,14,17 In Bangladesh, a country with high burdens of both noncommunicable and infectious diseases, out-of-pocket payments remain the most important source of funding for health care. Health insurance in Bangladesh is limited to a few small-scale schemes sponsored by nongovernmental organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 16% of bypassers reported having to borrow money or sell household assets to finance delivery, a measure of financial hardship that can lead to impoverishment. 24 These data underline that access to higherlevel facilities is inequitable, with the wealthiest women more likely to obtain secondary services, and that despite the United Republic of Tanzania's policy of free delivery, out-of-pocket costs for transport lead to financial hardship for families seeking hospital care.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 The overall frequency of using such strategies were found to be more common among the poorest countries and those people with limited health insurance. 21 The consequences of these strategies very often keep households in debt or poverty for a long period of time after the illness that created the debt. 22 Towards Universal Coverage: Examining Costs of Illness, Payment, and Coping Strategies to Different Population Groups in Southeast Nigeria…”
Section: Introductionmentioning
confidence: 99%